Asuhan keperawatan pada lansia hipertensi dengan intervensi rendam kaki air hangat - Marhamah, Marhamah; Khairani, Khairani; Nurhasanah, Nurhasanah (PT WIM Solusi Prima, 2024)
Background: The increasing number of elderly individuals with various health problems poses a challenge in how to achieve healthy and independent seniors to minimize the burden on society and the state. The most common health issues experienced by the elderly are non-communicable diseases, including high blood pressure (hypertension), joint inflammation (osteoarthritis), diabetes (diabetes mellitus/DM), heart disease, stroke, chronic kidney failure and cancer. The prevalence of hypertension in Indonesia is 34.1 percent, an increase from 21.5 percent in 2013. Aim of Research: The purpose of this Final Scientific Paper is to provide nursing care to Mrs. Z with hypertension. The diagnoses adressed in this case are ineffective health management, anxiety and disturbed sleep patterns. Research Method: This research uses a case study conducted by home visit. Results of Study: The evaluation results of warm water soak for 5 days showed an effective impact on lowering Mrs. Z’s blood pressure. Conclusion: After being given the intervention, there was an increase in Mrs. Z's knowledge regarding the concept and practice of soaking feet in warm water so that Mrs. Z was motivated to continue non-pharmacological therapy. Latar Belakang: Peningkatan jumlah lansia dengan berbagai masalah kesehatan menjadi tantangan bagaimana dapat mewujudkan lansia yang sehat dan mandiri agar meminimalisir beban bagi masyarakat dan negara. Masalah kesehatan terbanyak yang dialami lansia adalah penyakit tidak menular diantaranya tekanan darah tinggi (hipertensi), peradangan sendi (osteoarthritis), kencing manis (diabetes melitus/DM), penyakit jantung, stroke, gagal ginjal menahun dan kanker. Prevelensi hipertensi di Indonesia sebesar 34,1 persen yang terjadi peningkatan dari sebelumnya 21,5 persen pada tahun 2013. Tujuan: Tujuan dari Karya Ilmiah Akhir ini yaitu untuk memberikan asuhan keperawatan kepada Ny. Z dengan hipertensi. Metode: Penelitian ini menggunakan studi kasus yang dilakukan dengan kunjungan rumah (home visit). Hasil: Hasil evaluasi implementasi pemberian terapi rendam air hangat selama 5 hari didapakan bahwa adanya pengaruh yang efektif terhadap penurunan tekanan darah Ny. Z. Kesimpulan: Setelah diberikan intervensi, adanya peningkatan pengetahuan Ny. Z terkait konsep dan praktik rendam kaki air hangat sehingga memotivasi Ny. Z untuk melanjutkan terapi non-farmakologis.